2008
DOI: 10.1007/s10029-008-0460-3
|View full text |Cite|
|
Sign up to set email alerts
|

The use of sterilised polyester mosquito net mesh for inguinal hernia repair in Ghana

Abstract: Polyester mosquito net mesh represents a cost-effective alternative to commercial meshes in developing countries, with a relatively low rate of early complications and similar short-term recurrence rates. The use of local anaesthesia may enhance this further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 15 publications
5
56
1
4
Order By: Relevance
“…The mechanical properties of this mesh, which normally serves as a mosquito net, are similar to those of widely available commercial surgical meshes. 21 The control group received a commercial 100% polypropylene mesh (Parietene Light), manufactured by Covidien. Both were lightweight meshes (the low-cost mesh weighed 38.0 g per square meter, and the commercial mesh weighed 53.7 g per square meter), and the pore size was similar in the two meshes (1.5 mm and 1.9 mm, respectively).…”
Section: Procedures and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical properties of this mesh, which normally serves as a mosquito net, are similar to those of widely available commercial surgical meshes. 21 The control group received a commercial 100% polypropylene mesh (Parietene Light), manufactured by Covidien. Both were lightweight meshes (the low-cost mesh weighed 38.0 g per square meter, and the commercial mesh weighed 53.7 g per square meter), and the pore size was similar in the two meshes (1.5 mm and 1.9 mm, respectively).…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…17,18 Mosquito meshes, which are similar to commercial meshes, are currently used in some places as a low-cost alternative in hernia repair. [19][20][21][22][23] Previous studies on the use of mosquito mesh in groin hernia repair have shown promising results with respect to tissue reaction, outcome, and cost-effectiveness. 19,[21][22][23][24][25][26] However, data from randomized trials are lacking to inform the safety and long-term effectiveness of this practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clarke et al report their results, implanting sterilized polyester mosquito net mesh in 95 poor patients in Ghana, with 2% infection and no recurrences. They concluded that PE mosquito net mesh is a cost-effective alternative to commercial mesh for use in inguinal hernia repair in developing countries (Clarke et al, 2009). Optimistic results were also described in a study performed before this one, in Burkina Faso, using Nylon (100% Polyamide 6-6) mosquito net mesh, this time describing the complete absence of infection (Freudenberg et al, 2006).…”
Section: Charity Campaigns Involving Biomaterials For Low Income Patimentioning
confidence: 96%
“…Calculations related to cost-eVectiveness included in the paper by Clarke et al [1] were drawn from a previous version of Shillcutt et al [2], which contained several errors that should be highlighted. The correct values within the following sentence are in parentheses: "DALYs were calculated in the reference case, with an average of 18.90 (9.32) DALYs averted per person, and a total of 2,136 (1,052) DALYs averted in the study.…”
Section: Dear Editorsmentioning
confidence: 99%